Perlindungan Hukum Investor Minoritas: Studi Kasus Pt Sri Isman Tbk - Pratama, Andreas Pandhita; Prastyanti, Rina Arum; Ningsih, Widi Nugraha (Universitas Muara Bungo, 2025)
This research aims to study the impact of the suspension of PT Sri Rejeki Isman Tbk share trading on shareholder investors, especially retail investors as minority shareholders. Formulation of the problem in this research: a) What are the forms of legal rules for the legal protection of investors in the Indonesian capital market? b) How can this legal and regulatory framework address the concerns of minority shareholders during suspension to delisting situations? This type of research is normative legal research or library research, namely a form of research that uses library materials as the main data source, in the form of books, notes or reports of research results from previous research. In the event of the suspension of PT Sri Rejeki Isman as a result of: a) Not paying coupons and principal of medium-term debt, b) Negative equity, c) Not publishing financial reports for the first quarter of 2022. In the event of this loss, OJK has the authority to supervise, audit and Protection can be present as a legal step that can be taken by shareholders who are consumers in the financial services sector. OJK is present as a place to complain about things that have not reached an agreement